El pesimismo de Schopenhauer en Borges: una herencia cristiana en común. - Plante, Claudia (Universidad Nacional del Litoral, 2021)
This paper aims to demonstrate that Schopenhauer’s pessimism, very pervasive in Borges’ work is deeply rooted in Christianism. After showing the similarities between the Christian and Schopenhauerian ideas, the extent to which Borges integrates them to his work or distances himself from them will be analized.